1994
DOI: 10.1192/bjp.164.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Prophylaxis of Bipolar Illness

Abstract: Using a longitudinal life-table analysis, we assessed the efficacy of lithium alone, administered within the context of a naturalistic clinical setting, by calculating the probability of patients remaining free of an affective episode (manic or depressive) over a five-year course. In addition, for those who suffered a manic or depressive relapse, we attempted to analyse the subsequent course of patients who suffered a manic/hypomanic or depressive relapse and were then restabilised on lithium plus either a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, the current findings do not represent treatment effectiveness in all candidates for lithium therapy: many patients with bipolar or schizoaffective disorders-particularly those now available for study at research centers-do not do well with lithium monotherapy, and many others refuse to consider it or fail to remain compliant with recommended doses (17,38). High rates of apparent treatment failure have been documented in several recent surveys, typically based on clinically complex samples in urban teaching centers (38,(45)(46)(47)(48)(49)(50). However, these have usually focused on the presence of recurrences rather than on reduction of morbidity and mortality, and their results are not consistently worse than those in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…However, the current findings do not represent treatment effectiveness in all candidates for lithium therapy: many patients with bipolar or schizoaffective disorders-particularly those now available for study at research centers-do not do well with lithium monotherapy, and many others refuse to consider it or fail to remain compliant with recommended doses (17,38). High rates of apparent treatment failure have been documented in several recent surveys, typically based on clinically complex samples in urban teaching centers (38,(45)(46)(47)(48)(49)(50). However, these have usually focused on the presence of recurrences rather than on reduction of morbidity and mortality, and their results are not consistently worse than those in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…First, the duration of stability required prior to randomization could be lengthened. One likely cost of this design modification is that the proportion of participants actually randomized would decrease further [109]. A second modification would be to gradually taper the discontinuation of medication among participants randomized to receive placebo.…”
Section: Discussionmentioning
confidence: 99%
“…A review of several controlled studies from the 1960s and 1970s reported lithium to fail on average in 33% of cases (Prien 1988b). Most recent controlled studies have shown higher failure rates, with 55% reported in a large multicenter double-blind controlled study (Prien et al 1984), and other naturalistic studies showing failure rates of 42 to over 70% (Dickson and Kendell 1986;Shapiro et al 1989;Harrow et al 1990;Tohen et al 1990a,b;Maj et al 1991;O'Connell et al 1991;Keller et al 1993;Peselow et al 1994;Coryell et al 1995). In a recent study of lithium prophylaxis in bipolar and schizoaffective patients (Coryell et al), high relapse rates were reported; the likelihood of at least one recurrence after 5 years exceeded 70%.…”
Section: Prophylaxis Of Bipolar Disordermentioning
confidence: 98%